Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Translating community perceptions and concerns into planning: climate change adaptation in Hooper Bay, Alaska - Joseph T. Molina; Agatha A. Napoleon; Estelle Angutekaraq Thomson; Colleen Timmer; Andre Simon; Agulria Smart; Billy Tinker-Smith; Nicole Schmitt; Chelsey Cook (Regional Environmental Change, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Sequence stratigraphy and relative sea level variations in Kaštela Bay, Dalmatian coast, Croatia, and implications for the submerged palaeolandscapes and archaeology of the late Pleistocene, marine isotope stage 3 and marine isotope stage 2 - Simon Fitch; Slavica Bosnjak; Jessica W. Cook Hale; Vedran Barbarić; Timothy A. Shaw; Tanghua Li (Quaternary Science Reviews, 2025)

Multi-temporal DEMs used to quantify the geomorphological impact of a late 20th century glacier re-advance at Schwarzberggletscher, Switzerland - Toby N. Tonkin; Nicholas G. Midgley; Simon J. Cook (Geomorphology, 2025)

Delivering nutrient management impact through farmer-centric research: a systematic review of innovation systems in African smallholder systems - Ivan S. Adolwa; Shamie Zingore; James Mutegi; Matthew McNee; Bolaji A. Akorede; Denver Masidza; T. Scott Murrell; Samuel Mathu Ndungu; Eileen Nchanji; Simon Cook; Thomas Oberthür (Agricultural Systems, 2025)

A new digital cover photography dataset and processing tool for SMAPVEX19-22: How siting and sky condition impact plant area index retrievals in continuous measurement set-ups - Simon Kraatz; Michael H. Cosh; V. Kelly; Laura Bourgeau-Chavez; Jisung Geba Chang; Chris Cook; Victoria A. Walker; Paul R. Siqueira; Andreas Colliander (Agricultural and Forest Meteorology, 2025)

Past and present bacterial communities in deglaciating northern latitude catchments reveal varied soil carbon sequestration potential - Saule Akhmetkaliyeva; Andrew P. Dean; Leon J. Clarke; Simon J. Cook; Sharon Ruiz Lopez; Robert B. Sparkes (Science of The Total Environment, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Deep learning of estuary salinity dynamics is physically accurate at a fraction of hydrodynamic model computational cost - Galen Gorski; Salme Cook; Amelia Snyder; Alison P. Appling; Theodore Thompson; Jared D. Smith; John C. Warner; Simon N. Topp (Limnology and Oceanography, 2024)
Salinity dynamics in the Delaware Bay estuary are a critical water quality concern as elevated salinity can damage infrastructure and threaten drinking water supplies. Current state‐of‐the‐art modeling approaches use hydrodynamic models, which can produce accurate results but are limited by significant computational costs. We developed a machine learning (ML) model to predict the 250 mg L −1 Cl − isochlor, also known as the “salt front,” using daily river discharge, meteorological drivers, and tidal water level data. We use the ML model to predict the location of the salt front, measured in river miles (RM) along the Delaware River, during the period 2001–2020, and we compare predictions of the ML model to the hydrodynamic Coupled Ocean–Atmosphere‐Wave‐Sediment Transport (COAWST) model. The ML model predicts the location of the salt front with greater accuracy (root mean squared error [RMSE] = 2.52 RM) than the COAWST model does (RMSE = 5.36); however, the ML model struggles to predict extreme events. Furthermore, we use functional performance and expected gradients, tools from information theory and explainable artificial intelligence, to show that the ML model learns physically realistic relationships between the salt front location and drivers (particularly discharge and tidal water level). These results demonstrate how an ML modeling approach can provide predictive and functional accuracy at a significantly reduced computational cost compared to process‐based models. In addition, these results provide support for using ML models in operational forecasting, scenario testing, management decisions, hindcasting, and resulting opportunities to understand past behavior and develop hypotheses.

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Floods in Provence-Alpes-Côte d'Azur and lessons for French flood risk governance - Ioannis Kougkoulos; Myriam Merad; Simon J. Cook; Ioannis Andredakis (Natural Hazards, 2021)
France experiences catastrophic floods on a yearly basis, with significant societal impacts. In this study, we use multiple sources (insurance datasets, scientific articles, satellite data, and grey literature) to (1) analyze modern flood disasters in the PACA Region; (2) discuss the efficiency of French public policy instruments; (3) perform a SWOT analysis of French flood risk governance (FRG); and (4) suggest improvements to the FRG framework. Despite persistent government efforts, the impacts of flood events in the region have not lessened over time. Identical losses in the same locations are observed after repeated catastrophic events. Relative exposure to flooding has increased in France, apparently due to intense urbanization of flood-prone land. We suggest that the French FRG could benefit from the following improvements: (1) regular updates of risk prevention plans and tools; (2) the adoption of a build back better logic; (3) taking undeclared damages into account in flood risk models; (4) better communication between the actors at the different steps of each cycle (preparation, control, organization, etc.); (5) better communication between those responsible for risk prevention, emergency management, and disaster recovery; (6) an approach that extends the risk analysis outside the borders of the drainage basin; and (7) increased participation in FRG from local populations.

Quantifying the Effects of Aging on Morphological and Cellular Properties of Human Female Pelvic Floor Muscles - Mary Rieger; Pamela Duran; Mark Cook; Simon Schenk; Manali Shah; Marni Jacobs; Karen Christman; Deborah M. Kado; Marianna Alperin (Annals of Biomedical Engineering, 2021)

Geomorphology and geological controls of an active paraglacial rockslide in the New Zealand Southern Alps - Emma Cody; Daniel Draebing; Samuel McColl; Simon Cook; Marc-Andre Brideau (Landslides, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Origin and age of The Hillocks and implications for post‐glacial landscape development in the upper Lake Wakatipu catchment, New Zealand - Samuel T. McColl; Simon J. Cook; Timothy Stahl; Timothy R. H. Davies (Journal of Quaternary Science, 2019)
Ambiguous landscape histories can arise from equivocal or incomplete geomorphological, sedimentological or geochronological evidence. In this study, we apply quantitative analyses to robustly assess the origin and age of a field of rounded mounds, known as ‘The Hillocks’. Using clast analysis, the sediment is shown to be consistent with a landslide origin but inconsistent with other glacial sediments in the region. Cosmogenic 10 Be exposure age dating suggests The Hillocks formed ~8 ka. Ground‐penetrating radar reveals that the deposit rests upon deltaic foreset beds; combined with topographical data, we calculate a deposit volume of ~15–27 M m 3 , consistent with the estimated volume of the proposed source area. Overall, our data support a rock avalanche origin, indicating that by 8 ka the valley was ice‐free at The Hillocks’ location, and the level of Lake Wakatipu was lower than 340 m asl by this time. The Dart River delta shoreline was situated somewhere between The Hillocks and the present day shoreline at that time, and has prograded at a maximum average rate of 1 m a −1 since ~8 ka. These findings are significant given the lack of landforms by which to constrain glacial or post‐glacial landscape histories in this region of New Zealand. Copyright © 2019 John Wiley & Sons, Ltd.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Managing human-tiger conflict: lessons from Bardia and Chitwan National Parks, Nepal - Babu Ram Bhattarai; Wendy Wright; Damian Morgan; Simon Cook; Hem Sagar Baral (European Journal of Wildlife Research, 2019)

Modelling glacial lake outburst flood impacts in the Bolivian Andes - Ioannis Kougkoulos; Simon J. Cook; Laura A. Edwards; Leon J. Clarke; Elias Symeonakis; Jason M. Dortch; Kathleen Nesbitt (Natural Hazards, 2018)

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Effects of a common transcranial direct current stimulation (tDCS) protocol on motor evoked potentials found to be highly variable within individuals over 9 testing sessions - Jared Cooney Horvath; Simon J. Vogrin; Olivia Carter; Mark J. Cook; Jason D. Forte (Experimental Brain Research, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

A Framework for Quantitative Assessment of Impacts Related to Energy and Mineral Resource Development - Seth S. Haines; Jay E. Diffendorfer; Laurie Balistrieri; Byron Berger; Troy Cook; Don DeAngelis; Holly Doremus; Donald L. Gautier; Tanya Gallegos; Margot Gerritsen; Elisabeth Graffy; Sarah Hawkins; et al. (Natural Resources Research, 2014)

Convergent structure of multitrophic communities over three continents - Simon T. Segar; Rodrigo A. S. Pereira; Steve G. Compton; James M. Cook (Ecology Letters, 2013)
Astract Ecological theory predicts that communities using the same resources should have similar structure, but evolutionary constraints on colonisation and niche shifts may hamper such convergence. Multitrophic communities of wasps exploiting fig fruits, which first evolved about 75 MYA , do not show long‐term ‘inheritance’ of taxonomic (lineage) composition or species diversity. However, communities on three continents have converged ecologically in the presence and relative abundance of five insect guilds that we define. Some taxa fill the same niches in each community (phylogenetic niche conservatism). However, we show that overall convergence in ecological community structure depends also on a combination of niche shifts by resident lineages and local colonisations of figs by other insect lineages. Our study explores new ground, and develops new heuristic tools, in combining ecology and phylogeny to address patterns in the complex multitrophic communities of insect on plants, which comprise a large part of terrestrial biodiversity.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

An Investigation into the Rheology of Pharmaceutical Inter-granular Material Bridges at High Shear Rates - Barry Crean; Xinyong Chen; Simon R. Banks; Walter G. Cook; Colin D. Melia; Clive J. Roberts (Pharmaceutical Research, 2009)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. III. Colonization by birds - Clinton Schipper; Mike Shanahan; Simon Cook; Ian W. B. Thornton (Journal of Biogeography, 2001)
Location, Aim Long Island, 55 km north of New Guinea, erupted explosively in the seventeenth century and has been recolonized by animals and plants. Effectively in 1968, an island, Motmot, emerged from Long's 13 km‐diameter fresh‐water caldera lake, about 4 km from the nearest shore. A nested pair of colonization sequences is thus available for study. Long Island has been recolonized by birds, and Motmot has been colonized, presumably from the surrounding ring of Long Island. In order to monitor further colonization of Long Island following bird surveys in 1933 and 1972, and to survey the birds of Motmot, Motmot and the western parts of Long were visited for 15 days in 1999. Results In the last 66 years one species probably has become extinct; in the past 27 years three species have colonized and three, present in 1972, were not recorded in 1999. We assess the present number of nonmigrant land bird species as fifty. On Motmot, we recorded eight species, three breeding, and found two more only as prey remains (three raptor species were seen on the island). Main conclusions Long Island's avifauna still has youthful features. Species with good colonizing ability predominate, and there are no island‐endemic subspecies. There is a persistently high proportion of supertramps; none of the ten supertramps has been replaced by later‐colonizing ‘high‐S' species. A quasi‐equilibrium of about fifty species, fourteen fewer than the predicted equilibrium number for the island, has persisted for at least seven decades and may be seen as that appropriate to the present prolonged stage of Long's floral and vegetational development. Compared with the younger avifauna of Krakatau, Long's avifauna has a higher proportion of nectarivores, predators of large invertebrates and small vertebrates, and ground‐foraging insectivore‐herbivores, and a lower proportion of the insectivore‐frugivore guild. Motmot's small avifauna consists predominantly of species obtaining subsistence from outside the island.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. III. Colonization by birds - Clinton Schipper; Mike Shanahan; Simon Cook; Ian W. B. Thornton (Journal of Biogeography, 2001)

Are free amino acids responsible for the `host factor' effects on symbiotic zooxanthellae in extracts of host tissue? - Clayton B. Cook; Simon K. Davy (Hydrobiologia, 2001)

Identification and Characterization of Segments 3 and 4 of the ISAV Genome - Rachael J. Ritchie; Joël Heppell; Marcia B. Cook; Simon Jones; Steve G. Griffiths (Virus Genes, 2001)

Managing Uncertainty in Site-Specific Management: What is the Best Model? - Matthew L. Adams; Simon Cook; Robert Corner (Precision Agriculture, 2000)

Reduced Systemic Availability of an Antiarrhythmic Drug, Bidisomide, with Meal Co-administration: Relationship with Region-Dependent Intestinal Absorption - Li-Heng Pao; Simon Yuji Zhou; Chyung Cook; Tugrul Kararli; Carol Kirchhoff; James Truelove; Aziz Karim; David Fleisher (Pharmaceutical Research, 1998)